A Web-based Database for Drawings of Gods - Robert, Zhargalma Dandarova (Archive for the psychology of religion, 2016)
This original web-based database was developed at the University of Lausanne (Switzerland) as part of the international research project “Drawings of gods”, which explores children’s representations of supernatural agents. Its primary purpose is to store and organize data and metadata to be easily accessible to all affiliated researchers. However, anyone interested in the matter can view the drawings, as they were made publicly available. At present, our corpus is composed of over 5’100 drawings collected in different parts of the world (i.e., Japan, Russia, Switzerland, Romania, usa and Iran) and yet constantly developing.